Competitive advantages of multinational companies: A review of theoretical approaches - Pesalj Biljana (Međunarodni Problemi, 2011)
According to knowledge and network-based theories of multinational companies (MNCs), the main source of MNC competitive advantage is the creation and transfer of knowledge within the MNC system. The processes of knowledge creation and knowledge transfer are extensively investigated in the present literature. However, there are issues that are still underdeveloped, such as control and organizational mechanisms as a micro foundation of modern MNC theories. This paper is aimed at presenting an overview of the modern theoretical approaches of MNC competitive advantages from the managerial point of view. The applicability of these concepts is further considered in the case of MNC affiliates doing their business in transition economies in order to provide guidelines for future empirical research.